Kedudukan Filsafat Ilmu Dalam Perkembangan Teori dan Praktik Bimbingan Konseling - Adela, Nurul; Karneli, Yeni; Handayani, Puji Gusti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Guidance and counseling are vital components in education aimed at supporting holistic individual development. This article discusses the role of the philosophy of science as a philosophical foundation in the development of guidance and counseling theories and practices. The philosophy of science provides epistemological, ontological, and axiological frameworks that help in understanding the nature of knowledge, human reality, and ethical values underlying guidance and counseling services. With this understanding, guidance and counseling practices can be designed more holistically and effectively, addressing not only technical issues but also humanistic and professional aspects. This study employs a literature review method to analyze the contribution of the philosophy of science within the context of guidance and counseling, thereby supporting the development of meaningful and impactful services for individuals and society.